Expression and Function of the Homeostatic Molecule Del-1 in Endothelial Cells and the Periodontal Tissue - Jieun Shin; Kavita B. Hosur; Kalyani Pyaram; Ravi Jotwani; Shuang Liang; Triantafyllos Chavakis; George Hajishengallis (Clinical and Developmental Immunology)
Developmental endothelial locus-1 (Del-1) is an endothelial cell-secreted protein that limits the recruitment of neutrophils by antagonizing the interaction between the LFA-1 integrin on neutrophils and the intercellular adhesion molecule (ICAM)-1 on endothelial cells. Mice with genetic or age-associated Del-1 deficiency exhibit increased neutrophil infiltration in the periodontium resulting in inflammatory bone loss. Here we investigated additional novel mechanisms whereby Del-1 could interfere with neutrophil recruitment and inflammation. Treatment of human endothelial cells with Del-1 did not affect the expression of endothelial molecules involved in the leukocyte adhesion cascade (ICAM-1, VCAM-1, and E-selectin). Moreover, genetic or age-associated Del-1 deficiency did not significantly alter the expression of these adhesion molecules in the murine periodontium, further ruling out altered adhesion molecule expression as a mechanism whereby Del-1 regulates leukocyte recruitment. Strikingly, Del-1 inhibited ICAM-1-dependent chemokine release (CXCL2, CCL3) by neutrophils. Therefore, Del-1 could potentially suppress the amplification of inflammatory cell recruitment mediated through chemokine release by infiltrating neutrophils. Interestingly, Del-1 was itself regulated by inflammatory stimuli, which generally exerted opposite effects on adhesion molecule expression. The reciprocal regulation between Del-1 and inflammation may contribute to optimally balance the protective and the potentially harmful effects of inflammatory cell recruitment.